1992
DOI: 10.1111/j.1432-1033.1992.tb17507.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐chain and medium‐chain aliphatic‐ester synthesis in Saccharomyces cerevisiae

Abstract: In the yeast Saccharnmyces cerevisiae, the enzymes which catalyse the synthesis of ethyl acetate, ethyl n-hexanoate and isoamyl acetate were partly resolved from a fraction containing slowly sedimenting lipoproteins released during cell disruption with glass beads. Solubilization with detergents and fractionation by affinity chromatography have demonstrated the presence of at least three, and probably four, ester synthases which differ in their catalytic properties.Isoamyl-acetate synthase was solubilized and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
107
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 22 publications
(9 reference statements)
13
107
0
Order By: Relevance
“…These fatt y acids are important for beer flavour because they themselves are odour-active and can lead to rancid off -flavour at high concentrations. Moreover, they are also one of the starting materials for the synthesis of volatile esters (32). In general, fatt y acid production by Safale US-05 was higher than by NCYC 500 strain.…”
Section: Changes In Volatile Compositionmentioning
confidence: 95%
“…These fatt y acids are important for beer flavour because they themselves are odour-active and can lead to rancid off -flavour at high concentrations. Moreover, they are also one of the starting materials for the synthesis of volatile esters (32). In general, fatt y acid production by Safale US-05 was higher than by NCYC 500 strain.…”
Section: Changes In Volatile Compositionmentioning
confidence: 95%
“…Evolution of isoamyl alcohol (A) and isobutanol (B) levels during fermentation of wort brewed with 100% Scarlett or 50% Scarlett and 50% of dark malt (Melanoidin, Cara-aroma and roasted malt). Properties of these wort samples are presented in Table VII. are the key enzymes involved in the biosynthesis of acetate esters 15,25,27 . Deletion and overexpression studies indicated that the ATF1 gene is responsible for the formation of both isoamyl acetate and ethyl acetate, whereas ATF2 mainly leads to isoamyl acetate 35 .…”
Section: Fusel Alcohols and Estersmentioning
confidence: 99%
“…Similarly, Verstrepen et al (2003b) demonstrated that ATF2 deletion resulted in an 18% decrease in isoamyl acetate formation, while ATF2 overexpression resulted in a 6-to 8-fold increase. In consequence, the expression level of ATF2 in the current study was expected to be a limiting factor for ester synthesis in S. cerevisiae, confirming the hypothesis of Malcorps (Malcorps et al, 1991;Malcorps and Dufour, 1992). However, because different research groups have used different yeast strains and different fermentation conditions in ATF2 studies, it is difficult to compare results effectively.…”
Section: Introductionmentioning
confidence: 73%
“…The key enzymes involved in ester synthesis are alcohol acetyltransferases (AATases; EC 2.3.1.84) (Nordström, 1962(Nordström, , 1963(Nordström, , 1964. AATase II, which is encoded by ATF2, is 1 of the 2 main AATases in S. cerevisiae (Yoshioka and Hashimoto, 1981;Malcorps and Dufour, 1992;Fujii et al, 1994Fujii et al, , 1996aNagasawa et al, 1998;Yoshimoto et al, 1998Yoshimoto et al, , 1999. It catalyzes the formation of acetate esters from 2 substrates: an alcohol and an acetyl-CoA.…”
Section: Introductionmentioning
confidence: 99%